Chondrogenesis Defines Future Skeletal Patterns Via Cell Transdifferentiation from Chondrocytes to Bone Cells - Jing, Yan (Curr Osteoporos Rep, 2020)
PURPOSE OF REVIEW: The goal of this review is to obtain a better understanding of how chondrogenesis defines skeletal development via cell transdifferentiation from chondrocytes to bone cells. RECENT FINDINGS: A breakthrough in cell lineage tracing allows bone biologists to trace the cell fate and demonstrate that hypertrophic chondrocytes can directly transdifferentiate into bone cells during endochondral bone formation. However, there is a knowledge gap for the biological significance of this lineage extension and the mechanisms controlling this process. SUMMARY: This review first introduces the history of the debate on the cell fate of chondrocytes in endochondral bone formation; then summarizes key findings obtained in recent years, which strongly support a new theory: the direct cell transdifferentiation from chondrocytes to bone cells precisely connects chondrogenesis (for providing a template of the future skeleton, classified as phase I) and osteogenesis (for finishing skeletal construction, or phase II) in a continuous lineage-linked process of endochondral bone formation and limb elongation; and finally outlines nutrition factors and molecules that regulate the cell transdifferentiation process during the relay from chondrogenesis to osteogenesis.